(untitled) (Journal of Applied Oral Science, 2013)
No in situ protocol has assessed the dose-response effects of fluoride dentifrices involving low-fluoride formulations. Objective: To assess the ability of an in situ remineralization model in determining dose-response effects of dentifrices containing low fluoride concentrations ([F]) on bovine enamel. Material and Methods: Volunteers wore palatal appliances containing demineralized enamel blocks and brushed their teeth and devices with the dentifrices supplied (double-blind, crossover protocol) separately for 3 and 7 days. Surface hardness (SH), integrated subsurface hardness (ΔKHN) and [F] in enamel were determined. Data were analyzed by ANOVA, Tukey's test and Pearson's correlation (p